2010
DOI: 10.1111/j.1742-1241.2010.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral vitamin D and calcium replacement on glycaemic control in South Asian patients with type 2 diabetes

Abstract: This study shows that vitamin D and calcium replacement therapy in South Asian patients with T2DM causes a significant decrease in both HbA1c and weight, which may be attributed to the increase in vitamin D levels post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…While not truly representative of the Aboriginal population as a whole, our study participants included both staff and patients, and excluded people known to have diabetes, which was felt to be a reasonable compromise given the difficulties associated with recruiting a more formally representative sample. Assuming an effect size similar to previously published work, a sample size of 202 participants would have been required to properly examine the relationship between levels of vitamin D and fasting glucose 24 , 25 . Our sample was therefore too small for this purpose, and was also too small to confirm any negative effect of smoking on vitamin D status 26 , 27 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While not truly representative of the Aboriginal population as a whole, our study participants included both staff and patients, and excluded people known to have diabetes, which was felt to be a reasonable compromise given the difficulties associated with recruiting a more formally representative sample. Assuming an effect size similar to previously published work, a sample size of 202 participants would have been required to properly examine the relationship between levels of vitamin D and fasting glucose 24 , 25 . Our sample was therefore too small for this purpose, and was also too small to confirm any negative effect of smoking on vitamin D status 26 , 27 …”
Section: Discussionmentioning
confidence: 92%
“…Assuming an effect size similar to previously published work, a sample size of 202 participants would have been required to properly examine the relationship between levels of vitamin D and fasting glucose. 24,25 Our sample was therefore too small for this purpose, and was also too small to confirm any negative effect of smoking on vitamin D status. 26,27 In summary, vitamin D insufficiency is common in this population of adult Aboriginal Australians, as indicated by the low mean serum 25-OHD level overall and low mean levels found in all seasons other than summer.…”
Section: Public Healthmentioning
confidence: 92%
“…A response to this challenge follows in the study by Sabherwal et al. in this journal (3). They found that increasing the levels of vitamin D in South Asian patients with type 2 diabetes does indeed have the effect of producing a significant reduction in the HbA1c and patient weight in those deficient in this vitamin.…”
mentioning
confidence: 97%
“…Sabherwal, Bravis, & Devendra (2010) reported conflicting data who performed a similar study using South Asian patients with T2D. In this research, the authors found that vitamin D supplementation decreased both A1c levels and weight.…”
Section: Vitamin D Insulin Secretion Sensitivity and Resistancementioning
confidence: 60%
“…Data collected for this investigation was obtained from retrospective chart analysis of patients that had and had not received vitamin D and calcium supplementation. Sabherwal et al (2010) found that while vitamin D was important in reducing A1c and weight, the moderating role of calcium in these processes must also be reviewed. Based on the available data, the authors were not able to separate out the specific role of vitamin D in reducing A1c.…”
Section: Vitamin D Insulin Secretion Sensitivity and Resistancementioning
confidence: 99%